2021
DOI: 10.1007/s00148-021-00835-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantity and quality of childcare and children’s educational outcomes

Abstract: Policy-makers wanting to support child development can choose to adjust the quantity or quality of publicly funded universal pre-school. To assess the impact of such changes, we estimate the effects of an increase in free pre-school education in England of about 3.5 months at age 3 on children’s school achievement at age 5. We exploit date-of-birth discontinuities that create variation in the length and starting age of free pre-school using administrative school records linked to nursery characteristics. Estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Andrew et al (2019) show that improvements in pedagogical methods can have a significantly positive impact on child development within a randomised controlled trial (RCT) framework. Blanden et al (2022) find that an additional term of free pre-school education in England has a substantially larger impact on age 5 children's school achievement if this education is received in settings with the highest inspection ratings, though the authors are not able to pinpoint the specific practices which lead to enhanced child development. There is some evidence from the EPPSE project (Effective Pre-School, Primary and Secondary Education), a longitudinal UK study funded by the Department for Education, that attending high-quality pre-school (versus lowquality) is beneficial for children's academic and social outcomes through age 16, mainly for disadvantaged children (Department for Education, 2015).…”
Section: 1mentioning
confidence: 84%
“…Andrew et al (2019) show that improvements in pedagogical methods can have a significantly positive impact on child development within a randomised controlled trial (RCT) framework. Blanden et al (2022) find that an additional term of free pre-school education in England has a substantially larger impact on age 5 children's school achievement if this education is received in settings with the highest inspection ratings, though the authors are not able to pinpoint the specific practices which lead to enhanced child development. There is some evidence from the EPPSE project (Effective Pre-School, Primary and Secondary Education), a longitudinal UK study funded by the Department for Education, that attending high-quality pre-school (versus lowquality) is beneficial for children's academic and social outcomes through age 16, mainly for disadvantaged children (Department for Education, 2015).…”
Section: 1mentioning
confidence: 84%
“…The study found that the expansion led to severe negative effects on child-adult interactions. Similarly, studying the introduction of free part-time centre-based childcare in England, Blanden et al (2022) found significant improvements in educational attainment by the age of five, with the largest impacts in settings with the highest inspection quality ratings.…”
Section: Interventions Providing High Quality Inputsmentioning
confidence: 95%
“…The greatest benefit is found among children who start at ages 2-3, with heterogeneous effects according to family income and race. Blanden et al (2022) analyse the effect of an additional 3.5 months of preschool education at age 3 in England on children's school achievement at age 5 and find similar positive effects, as well as a "fading out effect" by age 7. Cornelissen and Dustmann (2019) instead look at the effects of additional schooling before age 5 resulting from changes in school entry rules.…”
Section: Introductionmentioning
confidence: 95%